Design and validation of bending test method for characterization of miniature pediatric cortical bone specimens. (February 2013) - Albert, Carolyne I; Jameson, John; Harris, Gerald
Osteogenesis imperfecta is a genetic disorder of bone fragility; however, the effects of this disorder on bone material properties are not well understood. No study has yet measured bone material strength in humans with osteogenesis imperfecta. Small bone specimens are often extracted during routine fracture surgeries in children with osteogenesis imperfecta. These specimens could provide valuable insight into the effects of osteogenesis imperfecta on bone material strength; however, their small size poses a challenge to their mechanical characterization. In this study, a validated miniature three-point bending test is described that enables measurement of the flexural material properties of pediatric cortical osteotomy specimens as small as 5 mm in length. This method was validated extensively using bovine bone, and the effect of span/depth aspect ratio (5 vs 6) on the measured flexural properties was examined. The method provided reasonable results for both Young's modulus and flexural strength in bovine bone. With a span/depth ratio of 6, the median longitudinal modulus and flexural strength results were 16.1 (range: 14.4–19.3) GPa and 251 (range: 219–293) MPa, respectively. Finally, the pilot results from two osteotomy specimens from children with osteogenesis imperfecta are presented. These results provide the first measures of bone material strength in this patient population.